CLINICAL ASSESSMENT OF ALAMBUSHADI CHURNA AND DWIPANCHMULADHYA TAIL VASTI IN THE MANAGEMENT OF AMAVATA VIS-A-VIS RHEUMATOID ARTHRITIS (AYUSHDHARA, 2019)
Amavata is a chronic immune inflammatory systemic disorder mainly affecting synovial joints, caused due to formation of Ama and its association with vitiated Dosha and deposition in Shleshma sthana i.e. joints. Clinical features of Amavata resembles with Rheumatoid Arthritis, it poses a challenge for the physician owing to its chronicity, morbidity and complications. The treasure of Ayurveda therapeutics has laid out detailed treatment line for Amavata. Hence to establish a firm scientific basis for classical Ayurvedic formulation is now being felt. Keeping in view the above concepts, the research work entitled Clinical Assessment of Alambushadi Churna and Dwipanchmuladhya Tail Vasti in the Management of Amavata vis-a-vis Rheumatoid Arthritis.The sample of 60 patients presenting with classical signs and symptoms of Aamavata according to Ayurvedic classics, after subjection to modern parameters were subdivided randomly into four groups. Out of 60 patients only 51 patients completed the follow up study in which group A (Alambushadi churn orally) consist of 13 patients, group B (Matra Vasti by Dwipanchmuladhya Tail), consist of 12 patients group C (Alambushadi Churn orally) consist of 13 patients and group D (methotrexate Folic Acid) consist of 13 patients.The research work and the Ayurvedic management schedule of Matra Vasti and Alambushadi churna can be used in the chronic as well as acute patients of Amavata with fruitful results.